Influence of the Redesign of the Production Processes of a Flexible Packaging Company Based on Continuous Improvement - Aldea Molina, Andrea Lizzeth (2021)
The company under study aimed to reduce the scrap rates of each process of flexible packaging manufacturing, originated as a result of poor procedures, returned products, and observed spools and/or bales. A reduction in claims was also expected as a result of the improvement in the quality of the finished product. The reduction of scrap in each process of the plastics división led to a reduction in reprocessing and costs. This, in turn, had a positive impact on the company’s income as the provision of high quality products resulted in customer loyalty. Furthermore, processes in the areas of extrusion, printing, cutting, laminating and sealing were made more efficient. The standardization of procedures and processes improved their execution time, creating a more positive image for customers and competitors.